Eksistensi Digital Nomad dalam Perspektif Hukum Ketenagakerjaan Indonesia: Antara Peluang Investasi dan Pengaburan Makna Hubungan Kerja - Chandra Devaraihan Wahyudi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This article examines the existence of digital nomads in Indonesia from the perspective of employment law, focusing on the contradiction between immigration policies such as the E-Visa Remote Worker that support remote work and the definition of employment relationships in the Employment Law that requires local sponsors. Using a normative juridical approach, the research analyzes existing legal gaps, the implications of blurring the meaning of employment relationships on worker protections such as Occupational Health and Safety (K3) and social security, as well as the potential loss of state revenue from income tax (PPh 21). The findings indicate that digital nomads are in a legal gray area that requires specific regulations (lex specialis) to integrate local economic investment opportunities with public obligations. Recommendations include harmonizing immigration and employment regulations, with comparative policies from countries like Estonia and Portugal, to create an adaptive framework that supports digital innovation without compromising legal sovereignty.